Equal Pay Act - cartoon, 1982 (1982)
1982 1960-2000 "Equal Pay Act - cartoon, 1982" [EP0112], 1982 This cartoon by Phil Evans, showing a cleaner discovering that the Equal Pay Act has been swept under a carpet, is from a 1982 Trade Union Resource Centre publication 'Can job evaluation help women to win equal pay?'